Manajemen Risiko Fungsi Pengawasan pada Wilayah Kerja Kantor Kesyahbandaran dan Otoritas Pelabuhan Kelas I Tanjung Emas Semarang - Perkasa, Muhammad Isnanda Bintang; Amrullah, Romanda Annas; Gupron, Akhmad Kasan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Risk Management in the Supervisory Function activities at the Harbormaster and Port Authority Office Class I Tanjung Emas Semarang is carried out to find and measure the risks that occur, this study also aims to develop control methods that aim to improve supervisory performance. The method used in data collection is a mixed method with a quantitative approach through questionnaires and risk matrices and qualitative through interviews and observations. In the data analysis of this study, brainstorming analysis was used to identify risks, risk matrix analysis was used to measure the level of risk, and interviews with the KSOP were used for risk control strategies. The results of the study showed that most of the risks were in the moderate to high category, especially in terms of compliance with standard operating procedures (SOPs), use of personal protective equipment (PPE), and readiness of human resources (HR). By implementing structured risk management, KSOP Class I Tanjung Emas is expected to increase the effectiveness and suitability of the implementation of supervisory functions and create a safe, orderly and good port work environment.